2020
DOI: 10.1002/mp.14371
|View full text |Cite
|
Sign up to set email alerts
|

Dilated conditional GAN for bone suppression in chest radiographs with enforced semantic features

Abstract: Purpose The purpose of this essay is to improve computer‐aided diagnosis of lung diseases by the removal of bone structures imagery such as ribs and clavicles, which may shadow a clinical view of lesions. This paper aims to develop an algorithm to suppress the imaging of bone structures within clinical x‐ray images, leaving a residual portrayal of lung tissue; such that these images can be used to better serve applications, such as lung nodule detection or pathology based on the radiological reading of chest x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Most of the papers surveyed in this work train and test their method on data from the same domain. This finding is inline with the previously reported studies (Kim et al, 2019; Conditional GAN and two variational autoencoders designed for CXR generation PR Gomi et al (2020) Novel reconstruction algorithm for CXR enhancement PR Zhou et al (2020b) Bone shadow suppression using conditional GANS with dilated U-Net variant BS J Matsubara et al (2020) Generates CXRs from CT to train CNN for bone suppression BS PR Zunair and Hamza (2021) Generates COVID-19 CXR images to improve network training and performance CV CC,RP Bayat et al (2020) 2D-to-3D encoder-decoder network for generating 3D spine models from CXR studies Z PR Bigolin Lanfredi et al (2020) Generates normal from abnormal CXRs, uses the deformations as disease evidence Z PR Prevedello et al, 2019) and highlights an important concern: most of the performance levels reported in the literature might not generalize well to data from other domains (Zech et al, 2018). Several studies (Yao et al, 2019;Zech et al, 2018;Cohen et al, 2020b) demonstrated that there was a significant drop in performance when deep learning systems were tested on datasets outside their training domain for a variety of CXR applications.…”
Section: Domain Adaptationsupporting
confidence: 88%
See 3 more Smart Citations
“…Most of the papers surveyed in this work train and test their method on data from the same domain. This finding is inline with the previously reported studies (Kim et al, 2019; Conditional GAN and two variational autoencoders designed for CXR generation PR Gomi et al (2020) Novel reconstruction algorithm for CXR enhancement PR Zhou et al (2020b) Bone shadow suppression using conditional GANS with dilated U-Net variant BS J Matsubara et al (2020) Generates CXRs from CT to train CNN for bone suppression BS PR Zunair and Hamza (2021) Generates COVID-19 CXR images to improve network training and performance CV CC,RP Bayat et al (2020) 2D-to-3D encoder-decoder network for generating 3D spine models from CXR studies Z PR Bigolin Lanfredi et al (2020) Generates normal from abnormal CXRs, uses the deformations as disease evidence Z PR Prevedello et al, 2019) and highlights an important concern: most of the performance levels reported in the literature might not generalize well to data from other domains (Zech et al, 2018). Several studies (Yao et al, 2019;Zech et al, 2018;Cohen et al, 2020b) demonstrated that there was a significant drop in performance when deep learning systems were tested on datasets outside their training domain for a variety of CXR applications.…”
Section: Domain Adaptationsupporting
confidence: 88%
“…(Gozes and Greenspan, 2019;Baltruschat et al, 2019a). More sophisticated pre-processing steps to improve model performance include bone suppression (Baltruschat et al, 2019b;Zhou et al, 2020b) and lung cropping (Liu et al, 2019).…”
Section: Image-level Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we used a bone suppression model based on the GAN framework to maintain the similarity between the target and generation domains [ 20 ]. The GAN can optimize image generators by adding discriminators as assisting components during training sessions [ 29 ]. To prevent image blurring, our model was designed to learn the frequency details of original images more effectively through the Harr 2D wavelet decomposition of the input data.…”
Section: Discussionmentioning
confidence: 99%